Drying sea buckthorn berries (Hippophae rhamnoides L.): Effects of different drying methods on drying kinetics, physicochemical properties, and microstructure - Geng, Zhihua; Zhu, Lichun; Wang, Jun; Yu, Xianlong; Li, Mengqing; Yang, Wenxin; Hu, Bin; Zhang, Qian; Yang, Xuhai (Frontiers in Nutrition, 2023)
Fresh sea buckthorn berries have a high moisture content and are perishable; therefore, drying is one of the most important techniques for extending their shelf life. Here, we investigated the effects of hot-air drying (HAD), infrared drying (IRD), infrared-assisted hot-air drying (IR-HAD), pulsed-vacuum drying (PVD), and vacuum freeze-drying (VFD) on the drying kinetics, microstructure, and physicochemical properties (color, non-enzyme browning index, rehydration ratio, and total phenol, total flavonoid, and ascorbic acid contents) of sea buckthorn berries. The results showed that the IR-HAD time was the shortest, followed by that of HAD, IRD, and PVD, while that of VFD was the longest. The VFD- and PVD-dried sea buckthorn berries had better physicochemical properties compared to HAD, IRD, and IR-HAD. Overall, VFD and PVD had higher ascorbic acid and total phenolic contents, better rehydration ability, and brighter color; however, considering the higher cost of VFD, we suggest that PVD is an optimal drying technology for sea buckthorn berries with the potential for industrial application.